The waste lands - King, Stephen, 1947- (King, Stephen, 1947- Dark tower, 2016)
Roland, the Last Gunslinger, and his companions--Eddie Dean and Susannah--cross the desert of damnation, drawing ever closer to the Dark Tower, a legion of fiendish foes, and revelations that could alter the world.